Glycopeptidolipids, a Double-Edged Sword of the Mycobacterium abscessus Complex - Gutiérrez, Ana Victoria; Viljoen, Albertus; Ghigo, Eric; Herrmann, Jean-Louis; Kremer, Laurent (Frontiers in Microbiology, 2018)
Mycobacterium abscessus is a rapidly-growing species causing a diverse panel of clinical manifestations, ranging from cutaneous infections to severe respiratory disease. Its unique cell wall, contributing largely to drug resistance and to pathogenicity, comprises a vast panoply of complex lipids, among which the glycopeptidolipids (GPL) have been the focus of intense research. These lipids fulfill various important functions, from sliding motility or biofilm formation to interaction with host cells and intramacrophage trafficking. Being highly immunogenic, the induction of a strong humoral response is likely to select for rough low- GPL producers. These, in contrast to the smooth high-GPL producers, display aggregative properties, which strongly impacts upon intracellular survival. A propensity to grow as extracellular cords allows these low-GPL producing bacilli to escape the innate immune defenses. Transitioning from high-GPL to low-GPL producers involves mutations within genes involved in biosynthesis or transport of GPL. This leads to induction of an intense pro-inflammatory response and robust and lethal infections in animal models, explaining the presence of rough isolates in patients with decreased pulmonary functions. Herein, we will discuss how, thanks to the generation of defined GPL mutants and the development of appropriate cellular and animal models to study pathogenesis, GPL contribute to M. abscessus biology and physiopathology.